Quantitative analysis of the polishing performance of Wurtzite-SiC surface texture on surface quality and material removal rate - Do, Tan-Tai; Le, Phu-Cuong; Fang, Te-Hua (Tribology international, 2024)
Molecular dynamics simulation is used to study Wurtzite-SiC's structural changes after polishing process. For realistic planarization conditions, various surface-textured structures are also used. Polishing speed greatly impacts dislocation distribution. Increasing velocity to 2 Å/ps reduces dislocation length from 800 to 500 Å quickly. Increasing polishing depth from 15 to 30 Å improves surface roughness by 25 %. Besides, textures such as RPrt-s (Rectangular prism textured) and TPrt-s (Triangular prism textured) show surface improvement but still result in high values greater than 42 Å. The amorphous transition rate (ATR) and material removal rate (MRR) closely correlate and display similar variations. The material's triangular prism textured surface enables for minimal SDL (subsurface damage layer) thickness, dislocation density, and atom removal while preserving low groove surface roughness. [Display omitted] •A depth of 2.5 nm is considered the most optimal for the polishing setup of wurtzite-SiC material.•The testing velocity of 1.5 Å/ps allows for removing more atoms from the material surface while still resulting in a surface with low roughness.•The TPyt-s provide a thick SDL layer under the material surface, making TPrt-s substrates best for planarization quality control.•Controlling the quantities of amorphous and removal atoms can be easily achieved by varying the polishing velocity.